Comparison of Sports Habits and Attitudes in University Students of Physical and Sports Education of Mostaganem (Algeria) and Physical Activity and Sport Sciences of León (Spain) - Zubiaur, Marta; Zitouni, Abdelkader; Del Horno, Saray (Frontiers in Psychology, 2021)
Background: In their professional practice, teachers can exert a strong influence on students, promoting healthy habits for life through the example of their own lifestyle. The aim of this study was to compare sports habits and attitudes in Physical Activity and Sports Education students at the universities of León (Spain) and Mostaganem (Algeria). Methods: We administered the “Motivations and Attitudes towards Physical Activity and Sports” questionnaire (in Spanish MIAFD) to 125 Algerian university students from the Institute for Physical Education and Sport (age: 21.87 + 2.51) and 122 Spanish university students (age: 22.98 + 2.36) from the Faculty of Physical Activity and Sport Science. Results: Chi-square tests showed significant differences (p< .001) with a large effect size (Cramer’s V: .650) in perceptions of sport and satisfaction with participation. Conclusions: The students from Mostaganem and Leon show many similarities, such as the number of female students in physical education and sport is quite small compared to male students. Both consider that universities should improve sports facilities to promote good practice. The practice of sports by our university students is far superior to that of students with other degrees, suggesting that they will set a good example of healthy habits once they enter their profession. Nevertheless, the participation of female Algerian students in sport was lower than that of Spanish students, and students at León showed more intrinsic motivation for participating in sport than their counterparts at Mostaganem.